An RNAi Screen Identifies New Genes Required for Normal Morphogenesis of Larval Chordotonal Organs - Abeer Hassan; Yael Timerman; Rana Hamdan; Nitzan Sela; Adel Avetisyan; Naomi Halachmi; Adi Salzberg (G3: Genes, Genomes, Genetics, 2018)
The proprioceptive chordotonal organs (ChO) of a fly larva respond to mechanical stimuli generated by muscle contractions and consequent deformations of the cuticle. The ability of the ChO to sense the relative displacement of its epidermal attachment sites likely depends on the correct mechanical properties of the accessory (cap and ligament) and attachment cells that connect the sensory unit (neuron and scolopale cell) to the cuticle. The genetic programs dictating the development of ChO cells with unique morphologies and mechanical properties are largely unknown. Here we describe an RNAi screen that focused on the ChO’s accessory and attachment cells and was performed in 2nd instar larvae to allow for phenotypic analysis of ChOs that had already experienced mechanical stresses during larval growth. Nearly one thousand strains carrying RNAi constructs targeting more than 500 candidate genes were screened for their effects on ChO morphogenesis. The screen identified 31 candidate genes whose knockdown within the ChO lineage disrupted various aspects of cell fate determination, cell differentiation, cellular morphogenesis and cell-cell attachment. Most interestingly, one phenotypic group consisted of genes that affected the response of specific ChO cell types to developmental organ stretching, leading to abnormal pattern of cell elongation. The ‘cell elongation’ group included the transcription factors Delilah and Stripe, implicating them for the first time in regulating the response of ChO cells to developmental stretching forces. Other genes found to affect the pattern of ChO cell elongation, such as αTub85E, β1Tub56D, Tbce, CCT8, mys, Rac1 and shot, represent putative effectors that link between cell-fate determinants and the realization of cell-specific mechanical properties.